Investigation of the influence of Pt/C percentage and humidity on the voltage decay rate of proton exchange membrane fuel cell. Issue 1 (18th December 2022) - Mathan, C.; Karthikeyan, P.; Dineshkumar, P.; Thanarajan, K.
Abstract: Voltage degradation is the main parameter that determines the effective usable life of a fuel cell, here the influence of Pt/C% and relative humidity (RH%) on the voltage decay rate of a fuel cell is experimentally evaluated and reported. This study implements a stress test with frequent interrupts of purging for determining the durability of the fuel cells. In the course of the 1456 h stress test for each membrane electrode assembly (MEA), the polarization curve and electrochemical impedance spectroscopy (EIS) were measured. The experimental results make it evident that the lowest voltage degradation was 6 µV/h for MEA with 40% Pt/C tested under 70% RH while the highest was 183 µV/h recorded for MEA with 20% Pt/C tested under 90% RH. From EIS results, the ohmic resistance increased for all the tested MEAs, which is also reflected in the performance degradation. Field emission scanning electron microscopy images also indicate the delamination of MEA layers which in turn increases the electron transfer resistance. So, the decisive factors for the fuel cell performance degradation were flooding, catalyst surface contamination, and delamination of MEA layers due to repeated mechanical and chemical stresses.